2019
DOI: 10.1177/1936724419846198
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Quality Education with Inclusive Human Development: Empirical Evidence from Sub-Saharan Africa

Abstract: This study examines the importance of inclusive human development in promoting education quality in a panel of 49 sub-Saharan African countries for the period 2000–2012. The empirical evidence is based on ordinary least squares (OLS), fixed effects (FE), and quantile regression (QR) estimations. It is apparent from the OLS and FE findings that inclusive human development has a negative effect on the outcome variable. This negative effect implies that inclusive human development improves education quality. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In another study, [35] found that availability and accessibility of finance mitigate income inequality in both urban and rural areas. Whereas, [36] reported that inclusive sustainable human development promotes quality human capital in sub-Saharan Africa. Moreover, financial inclusion found to promote human development [14,16,21,37,38] Contrarily, [15] show that financial inclusion has no connection with poverty and sustainable human development in south east Asia, while, it has increasing effect on income inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another study, [35] found that availability and accessibility of finance mitigate income inequality in both urban and rural areas. Whereas, [36] reported that inclusive sustainable human development promotes quality human capital in sub-Saharan Africa. Moreover, financial inclusion found to promote human development [14,16,21,37,38] Contrarily, [15] show that financial inclusion has no connection with poverty and sustainable human development in south east Asia, while, it has increasing effect on income inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, we examine the non-linear effect of remittances and ICT on pension income coverage, following the empirical framework used in Asongu et al (2019b) and Asongu and Odhiambo (2019). Using both OLS and FE specifications with pension income coverage as the dependent variable, we employ the quadratic term of both remittances and ICT while controlling for various pensioners' and country characteristics.…”
Section: Ordinary Least Squares and Fixed Effects Regressionsmentioning
confidence: 99%
“…coverage, following the empirical framework used in Asongu et al (2019b) and Asongu and Odhiambo (2019). Using both OLS and FE specifications with pension income coverage as the dependent variable, we employ the quadratic term of both remittances and ICT while controlling for various pensioners' and country characteristics.…”
Section: Ordinary Least Squares and Fixed Effects Regressionsmentioning
confidence: 99%